DIGITISING TO MEET SUSTAINABLE DEVELOPMENT GOALS: CHALLENGES IN THE AFRICAN CONTEXT - Zindi, Beauty; Ndhlovu, Emmanuel (Faculty of Business, Widya Mandala Surabaya Catholic University, Indonesia, 2024)
The advent of the Fourth Industrial Revolution (4IR) wields much potential to revolutionise operations and activities and fast-track the attainment of Sustainable Development Goals (SDGs). However, for developing regions like Africa, several factors impeding a full-swing technological revolution exist. Drawing on a qualitative semi-systematic literature review and underpinned by thematic data analysis, this article explored the challenges of deploying 4IR tools to fast-track the attainment of SDGs. The findings show that limited internet access, underdeveloped ICT infrastructure, regulatory barriers, lack of awareness and education, and lack of collaboration and data sharing are some of the challenges impeding digital adoption to meet SDGs in Africa. To fast-track technology uptake and increase the possibility of achieving SDGs before the 2030 deadline, it is recommended that African governments intervene. This is because the majority of businesses and households in Africa, are unable to afford digitalisation. Most of the households are smallholder farmers. Assisting these farmers with technology would help them increase production and thus, help eliminate hunger, reduce poverty, gender inequality, promote industry, innovation, and infrastructure, and 12 responsible consumption and production.